Amygdala activation during emotional face processing in adolescents with affective disorders: the role of underlying depression and anxiety symptoms - van den Bulk, Bianca G.; Meens, Paul H. F.; van Lang, Natasja D. J.; de Voogd, E. L.; van der Wee, Nic J. A.; Rombouts, Serge A. R. B.; Crone, Eveline A.; Vermeiren, Robert R. J. M. (Frontiers in Human Neuroscience, 2014)
Abstract Depressive and anxiety disorders are often first diagnosed during adolescence and it is known that they persist into adulthood. Previous studies often tried to dissociate depressive and anxiety disorders, but high comorbidity makes this difficult and maybe even impossible. The goal of this study was to use neuroimaging to test what the unique contribution is of depression and anxiety symptomatology on emotional processing and amygdala activation, and to compare the results with a healthy control group. We included 25 adolescents with depressive and/or anxiety disorders and 26 healthy adolescents. Participants performed an emotional face processing task while in the MRI scanner. We were particularly interested in the relation between depression/anxiety symptomatology and patterns of amygdala activation. There were no significant differences in activation patterns between the control group and the clinical group on whole brain level and ROI level. However, we found that dimensional scores on an anxiety but not a depression subscale significantly predicted brain activation in the right amygdala when processing fearful, happy and neutral faces. These results suggest that anxiety symptoms are a better predictor for differentiating activation patterns in the amygdala than depression symptoms. Although the current study includes a relatively large sample of treatment naïve adolescents with depression/anxiety disorders, results might be influenced by differences between studies in recruitment strategies or methodology. Future research should include larger samples with a more equal distribution of adolescents with a clinical diagnosis of depression and/or anxiety. To conclude, this study shows that abnormal amygdala responses to emotional faces in depression and anxiety seems to be more dependent on anxiety symptoms than on depression symptoms, and thereby highlights the need for more research to better characterize clinical groups in future studies.